2013
DOI: 10.5006/0948
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mg Content on the Sensitization and Corrosion of Al-xMg(-Mn) Alloys

Abstract: The influence of Mg content on the degree of sensitization (DoS) of Al-xMg-0.5Mn (wt%) alloys (where x varies from 3.36 wt% to 8.85 wt%) was investigated via the nitric acid mass loss test (NAMLT). NAMLT upon sensitized specimens revealed that mass loss was negligible below ~4.01 wt% Mg, while for Mg content ≥4.01 wt%, mass loss increased monotonically. The calculated equilibrium β-phase fractions were contrast with the DoS values. Additionally, the influence of the Mg content on corrosion was investigated via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 24 publications
2
35
0
2
Order By: Relevance
“…Characteristic electrochemical parameters are given in Table and potentiodynamic polarisation curves of the selected states are shown in Figure . The anodic polarisation curves do not show a sharp increase in the current density that would indicate the position of the pitting potential ( E pitt ), similarly to the behaviour observed in some Al–Mg and other Al alloys . Hence, in this study, E pitt has been determined as the potential at which the current increases by an order of magnitude upon a 10 mV potential change .…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Characteristic electrochemical parameters are given in Table and potentiodynamic polarisation curves of the selected states are shown in Figure . The anodic polarisation curves do not show a sharp increase in the current density that would indicate the position of the pitting potential ( E pitt ), similarly to the behaviour observed in some Al–Mg and other Al alloys . Hence, in this study, E pitt has been determined as the potential at which the current increases by an order of magnitude upon a 10 mV potential change .…”
Section: Resultssupporting
confidence: 59%
“…It is accepted that the IGC and SCC susceptibility increase is due to precipitation of anodic β‐(Al 3 Mg 2 ) phase at grain boundaries in the process known as sensitisation, although there are reports of SCC occurrence even in the absence of β‐(Al 3 Mg 2 ) phase precipitation . Sensitisation effects are uncommon in the alloys with Mg content below 3.5 wt%, but as the Mg content rises from 3.4 to 4 wt%, there is an abrupt increase in the IGC susceptibility . Further increase in the Mg content leads to linear, but less steep susceptibility increase .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that β phase precipitation and corrosion of Al alloys depend on the chemical composition121314, mechanical processing151617 , and elevated-temperature exposure1819. For example, Zhang et al studied the influence of grain size and grain orientation on the sensitization of Al 5083 processed by rolling, equal channel angular processing and high-pressure torsion17.…”
mentioning
confidence: 99%
“…As with most Al-alloys in which precipitation occurs, 5xxx alloy precipitates are often associated with (and are of greatest size at) grain boundaries 5 – 7 , where a lower barrier to nucleation exists. Some details specific to 5xxx series Al-alloys, which merit comment, are that (i) β-phase precipitation offers no age-hardening, instead causing weakening due to solute depletion from the matrix 8 , and (ii) β-phase precipitation also occurs intra granularly at heterogeneities including dislocations and Al x Mn dispersoids (noting that dispersoids are stable and do not respond to thermal exposure) 6 , 9 .…”
Section: Introductionmentioning
confidence: 99%